Analysis of the Influence of Information Quality and Communication Services of CNP LP3I Jakarta Depok Campus in Improving the Understanding of Level 3 Students about the World of Work - Dwimanda W, Dinda (The Eastasouth Management and Business, 2025)
Transitioning from academia to the professional world is a very critical phase for students, which requires a balance of academic knowledge and career readiness. This research explores how information quality and communication services affect the understanding of the professional world among third-year students at LP3I Jakarta Kampus Depok. The quantitative approach was utilized in this research, where the survey was conducted among 30 students, and the data analysis used multiple linear regression. The results showed that information quality and communication services significantly and positively influenced the students' career understanding, with a stronger effect from communication services. These variables jointly account for 78% of the variance in students' preparedness for the workforce. These findings underline the importance of accurate, relevant information and responsive communication in enhancing career readiness. The study provides practical recommendations for improving institutional services and contributes to the theoretical understanding of career preparation strategies.